Plan de negocios para la implementación de una nueva línea de productos para la empresa ferretería Eaga, cantón Quevedo, año 2014. - Paz Yánez, Celia Elizabeth (2015)
This research is conducted by an idea for improvement and business growth since the sale and distribution of materials and equipment hardware have become the basis for the architectural development of our country, which is why the need to expand the range of products Hardware in the portfolio of EAGA, but with guaranteed brand. It is therefore a market study was conducted at a random sample of 398 people in the economically active population (EAP) of Canton Quevedo, who expressed dissatisfaction when purchasing products, because in this area there is no hardware sells cement, iron and blocks; and hardware stores that have them are far away. In the technical study the micro and macro location of the project was established; the operational process, the system comprised of purchases and sales of the product and the resources established to carry out the project were also determined; the company logo "Hardware EAGA" was defined, which reflects a renewed business image with the slogan, "Hardware EAGA builder lights hand, the project implementation is being carried out by the high level of demand for these products required by our customers….